Data DeDuplication Using Optimized Fingerprint Lookup Method for Cloud Storage Using Android (International Journal of Engineering and Computer Science, 2017)
Today we all keep hearing about how fast data is being generated and also how important this data is to different organizations and enterprises. Hence organizations all around the globe are looking forward to storing this data in an efficient manner to avoid data loss and also to store all important information in a compressed and secure manner. Data Deduplication is an effective emerging technology that provides a solution to store more information in less space. As the advantages of offsite storage, less maintenance of storage infrastructure and cost benefits are very useful, huge enterprises choose to back up their data on cloud services. Data DeDuplication strategy aims at exploiting the fact that redundancy between two different types of data sets is minimal. By treating each application differently and storing the related information separately the overall disk usage can be improved to a great extent. This is done by implementing adaptive chunking, hashing and storing of different application separately. Data Conscious deduplication is observed to thus give a greater deduplication factor. It not only improves the deduplication process but also gives good bandwidth saving and efficient resource utilization essential for cloud storage.